(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2016)
A field experiment was conducted at Regional Agricultural Research Station, Bangladesh Agricultural Research Institute (BARI), Ishurdi, Pabna during two consecutive years of 2012-2013 and 2013-2014 to find out the suitable combination of intercropping of chili with sweet gourd for increasing the productivity and economic return. The treatments were T1=100% sweet gourd (2m x 2m) + 40% chili (50cm x 100cm) + 100% recommended fertilizer (RF) of chili, T2=100% sweet gourd (2m x 2m) + 40% chili (50cm x 100cm) + 75% RF of chili, T3=100% sweet gourd (2m x 2m) + 40% chili (50cm x 100cm) + 50% RF of chili, T4=100% sweet gourd (2m x 2m) + 50% chili (50cm x 80cm) + 100% RF of chili, T5=100% sweet gourd (2m x 2m) + 50% chili (50cm x 80cm) + 75% RF of chili, T6=100% sweet gourd (2m x 2m) + 50% chili (50cm x 80cm) + 50% RF of chili, T7=Sole sweet gourd, T8= Sole chili. The experiment was laid out in a randomized complete block design with three replications. Fruit yield was calculated for sweet gourd and chili in ton per hectare considering the whole plot as harvested area. Results revealed that the yield of both sweet gourd and chili significantly affected by plant population and fertilizer dose in the intercropping systems. The highest equivalent yield of sweet gourd (21.21 t ha-1), land equivalent ratio (1.59), gross return (Tk. 318150.00 ha-1), gross margin (Tk. 237935.00 ha-1) and benefit cost ratio (3.97) were obtained from 100% sweet gourd (2m x 2m) + 50% chili (50cm x 80cm) + 100% RF of chili (T4). Sole crop of chili (T8) gave the lowest equivalent yield of sweet gourd (7.38 t ha-1), gross return (Tk. 110700.00 ha-1), gross margin (Tk. 37455.00 ha-1) and benefit cost ratio (1.51). Therefore, sweet gourd (100%) and chili (50%) with recommended fertilizer (100%) of chili might be economically profitable for chili with sweet gourd intercropping system. Int. J. Agril. Res. Innov. & Tech. 5 (2): 64-69, December, 2015